Response to Disturbances in Soldier Beetles - Boyer, Matthew; Marshall, Jeremy (My University, 2017)
Studying insects’ response to disturbance can tell us how these organisms survive in hostile environments. Studies have shown that soldier beetles can have different mating behaviors depending on the species around them (Bernstein and Bernstein, 1999). They also exercise selective mating in changing ecological conditions (McLain, 2005). When disturbed, beetles are known to drop off plants onto the ground in order to get away from possible predators (Ben-Ari and Inbar, 2013). The goal of this experiment was to determine any trends in response to a probing disturbance by insects and more specifically, soldier beetles. I believed probing soldier beetles with a small disturbance would cause them to move away from the source of the disturbance, with individuals responding more than mating pairs. After collecting and analyzing the data, the conclusion is that the hypothesis is supported by having a greater reaction from individuals than mating pairs. These results suggest that an insect’s tolerance to disturbance increases when mating. This may lead to a decrease in survival behavior in order to fulfill mating interests.
Citation: Boyer, M. (2017). Response to Disturbances in Soldier Beetles . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.